A taxonomic review of the Indian species of the genus Eumenes Latreille (Hymenoptera: Vespidae: Eumeninae) - Kumar, Girish P.; Carpenter, James M.; Castro, Leopoldo; Sureshan, Pavittu M. (Zootaxa, 2017)
A taxonomic review of the Indian species of the genus Eumenes Latreille with a key to species is provided. The species Eumenes pomiformis (Fabricius, 1781) is recorded here for the first time from India, while E. affinissimus de Saussure, 1852, E. pomiformis (Fabricius, 1781) and E. persimilis Giordani Soika, 1960 are recorded from Pakistan. The reported distributions of seven species within India are augmented.